A signal fading-aware and data transmission estimation assisted handover mechanism in LTE networks. (2017) - Chang, Fu-Min; Wang, Hsiu-Lang; You, Wei-Hong; Kao, Shang-Juh
In Long-Term Evolution (LTE) networks, the connection between user equipment and base station may be lost when the user equipment moves out of the signal coverage by its service base station, therefore results in data loss. This paper proposes a radio signal fading-aware and data transmission estimation assisted handover mechanism in LTE networks in order to decrease the number of unnecessary handovers and data loss rate. Signal fading-aware mechanism is triggered to filter out interfering signal caused by fading in order to obtain the expected signal strength and thereby determine whether handover should be performed. The amount of data loss associated with signal fading is compared with the data loss associated with the handover in order to determine whether the handover procedure should be executed. Thus, if the user equipment performs a handover that is not triggered by signal fading, the handover wait time can be bypassed, whereas in the event of signal fading, handover is performed with the aim of minimising losses in data transmission. Simulation results demonstrate that 30% average handover times and 8% data loss rate are reduced, as compared with standard handover schemes.